2012
DOI: 10.1074/jbc.m111.336925
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate Is a Crucial Determinant for Skeletal Muscle Development/Regeneration and Improvement of Muscular Dystrophies

Abstract: Background: Expression level of chondroitin sulfate (CS) is important in embryonic development. However, its involvement in skeletal myogenesis is unknown. Results: The CS level is temporally decreased during skeletal muscle development, and its forced reduction enhances myogenic differentiation/regeneration. Conclusion: Temporal decline in CS levels is required for skeletal muscle differentiation/regeneration. Significance: Lowering CS abundance is a promising approach for skeletal muscle regenerative therapy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 45 publications
0
36
0
1
Order By: Relevance
“…32,33) The levels of extracellular and/or pericellular CS chains in differentiating C2C12 myoblast culture are dramatically reduced at the stage when multinucleated myotube formation begins in earnest, and this temporal reduction in CS chain abundance seems to be cell autonomously regulated by hyaluronidase-1, one of the CS catabolic enzymes. 34) Forced downregulation of CS, but not of hyaluronan, levels enhances myogenic differentiation in vitro and during myofiber regeneration in vivo in a mouse cardiotoxin-induced injury model. 34) Notably, in dystrophin-deficient mdx mice, a model of Duchenne muscular dystrophy, intramuscular injection of ChABC can ameliorate the dystrophic pathology that is characterized by widespread degeneration and recuperative regeneration of myofibers.…”
Section: Cs Has An Essential Role In Pluripotency Andmentioning
confidence: 96%
See 1 more Smart Citation
“…32,33) The levels of extracellular and/or pericellular CS chains in differentiating C2C12 myoblast culture are dramatically reduced at the stage when multinucleated myotube formation begins in earnest, and this temporal reduction in CS chain abundance seems to be cell autonomously regulated by hyaluronidase-1, one of the CS catabolic enzymes. 34) Forced downregulation of CS, but not of hyaluronan, levels enhances myogenic differentiation in vitro and during myofiber regeneration in vivo in a mouse cardiotoxin-induced injury model. 34) Notably, in dystrophin-deficient mdx mice, a model of Duchenne muscular dystrophy, intramuscular injection of ChABC can ameliorate the dystrophic pathology that is characterized by widespread degeneration and recuperative regeneration of myofibers.…”
Section: Cs Has An Essential Role In Pluripotency Andmentioning
confidence: 96%
“…34) Notably, in dystrophin-deficient mdx mice, a model of Duchenne muscular dystrophy, intramuscular injection of ChABC can ameliorate the dystrophic pathology that is characterized by widespread degeneration and recuperative regeneration of myofibers. 34) These findings indicate that CS abundance is a crucial determinant of skeletal muscle differentiation and regeneration and for improvement of muscular dystrophy; moreover, these findings may help elucidate the underlying mechanisms of Chn/CS-dependent embryonic cell division.…”
Section: Cs Has An Essential Role In Pluripotency Andmentioning
confidence: 99%
“…However, the involvement of hyaluronidases in CS catabolism has been estimated based on quantitative measurements of their hydrolytic activity toward CS variants in vitro [18]. Mikami et al [40] reported the involvement of HYAL1 in the degradation of CS at the stage of extensive syncytial myotube formation during muscle development. As described above, the storage of CS in HYAL1-deficient mice was demonstrated previously [34].…”
Section: Systemic Catabolism Of Csmentioning
confidence: 99%
“…No differences in the expression of the less well characterized hyaluronan receptor gene, hyaluronan-mediated motility receptor (Hmmr), also known as RHAMM, were observed (results not shown). Hyal1 has also recently been suggested to enhance myogenic differentiation by degrading chondroitin sulfate and allowing myoblast fusion (37); no changes in Hyal1 transcripts were observed with Has2 siRNA treatment.…”
Section: Hyaluronan Synthesis Inhibition Induces Alterations In Exprementioning
confidence: 99%